"Is this restaurant halal?" Surrogate indicators and Muslim behaviour. Issue 5 (25th July 2019) - Khan, Ghazala; Khan, Faiza
Abstract : Purpose: The purpose of this study is to investigate what cues or surrogate indicators Muslims use to determine whether restaurants are suitable for dining purposes in the absence of the halal logo and to examine if the cues used are different among Muslims from non-Muslim countries as opposed to Muslims from Muslim countries. Design/methodology/approach: Data were collected via semi-structured interviews in one Muslim majority (Malaysia) and one non-Muslim country (the UK). A total of 16 adults participated in the study with an equal representation from both countries. Findings: In the absence of the halal logo, participants relied on extrinsic cues such as the presence of other Muslim-looking customers and service personnel to determine whether a restaurant was deemed safe for dining in. The location of a restaurant was a strong indicator for Muslims in both Muslim and non-Muslim countries. In the absence of the halal logo, participants read the menus carefully, queried the service personnel for additional information and selected safer options, such as vegetarian and seafood. Research limitations/implications: The study used a small sample, and therefore, the findings are tentative. Practical implications: Given the growth of Muslim population in many non-Muslim countries, it is important for restaurants in non-Muslim countries not to marginalize this customer base. Trust is a key issue and service providers without the halal logo should gain the trust of Muslim customers by training service personnel and equipping them with knowledge of what halal means, developing menus with vegetarian and seafood options, providing detailed information on ingredients and communicating this on their websites and social media sites. They could also consider working with Muslim food and travel bloggers to promote themselves to a Muslim audience. They can develop a more Muslim sympathetic marketing approach and consider using separate cooking and serving utensils to gain trust and patronage of Muslim customers as well as to appeal to a larger market (vegans/vegetarians). Originality/value: The present study is one of the first studies that concentrates on gaining an insight into how Muslims make decision pertaining to the selection and dining at a restaurant in the absence of the halal logo. A major contribution of the study is the identification of cues that assist Muslims when evaluating and selecting alternative food options in the absence of a halal logo.